Correlation of Serum Nitric Oxide and Urine Malondialdehyde Levels in Non-Hemodialysis Chronic Kidney Disease Patients - Dinda Dwi Purwati; Arifa Mustika; Lukman Hakim; Mochammad Thaha (Cell and BioPharmaceutical Institute, 2022)
Background: In 2017, about 1.2 million people died because of Chronic Kidney Disease (CKD). Patients with CKD are known to have increased levels of oxidative stress which leads to decrease in NO production. NO is a highly reactive signaling molecule and a major determinant of vascular homeostasis. Thus, the decreased NO can be a risk factor for the development of atherosclerosis and increased cardiovascular risk. Meanwhile, Malondialdehyde (MDA) is known as excellent biomarker for oxidative stress. This study aims to determine the correlation of serum total nitric oxide (NO) and urine MDA levels in non-hemodialysis CKD patients.Materials and Methods: This study was an observational clinical study with a cross sectional design. Fourty-nine CKD subjects were selected by consecutive sampling. The samples for laboratory tests were collected from urine. MDA concentration was measured using the High-Performance Liquid Chromatography (HPLC) kit. NO concentration was measured with Griess reaction method and Total Nitric Oxide Parameter kit. The data were analyzed using the Statistic Package for Social Science (SPPS) software version 16.Results: The data showed significant negative correlations between MDA with NO (r=-0.294; p=0.041).Conclusion: There was a correlation between serum total NO and urine MDA levels in non-hemodialysis CKD patients.Keywords: chronic kidney disease, malondialdehyde, nitric oxide, non-hemodialysis